Effect of Environment, Social and Governance Disclosure on Firm Value - Faradilla Suretno; Fajri Adrianto; Mohamad Fany Alfarisi (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2022)
This study aims to determine the environmental, social, and governance of the firm value in this study are all companies listed on the Indonesia Stock Exchange from 2016-2020. The determination of the sample in this study used purposive sampling with the number of samples used by as many as 27 companies during the year. a period of 5 consecutive years of observation so that the total sample obtained is 135. This study uses Stata 14, the analytical technique used is panel data regression analysis. The results showed that the first hypothesis was found that the environment variable's disclosure had a positive and significant effect on firm value in companies listed on the Indonesia Stock Exchange. Social variable disclosure has a positive and significant impact on firm value in companies listed on the Indonesia Stock Exchange. Governance variable disclosure has a negative and significant impact on firm value in companies listed on the Indonesia Stock Exchange. While testing with the control variable, namely the company's size, partially has a significant negative effect on firm value, the leverage and profitability variables partially have a significant effect on firm value.